Focal buyer opportunism and farmers' market channel choice in the supply chain of mango in IGaCos, Philippines a transaction cost economic approach - Placencia, Shemaiah Gail P. (School of Management, University of the Philippines Mindanao, 2016)
Relationships among actors along the supply chain have a great influence in supply chain management. Focusing on the downstream node of the IGACoS mango supply chain, specially the bilateral relationships between farmers/contractors and their focal buyers, the bargaining power evidently leans towards the local buyers, hence creating a potential for them to become opportunistic. Taking off from lens of Transaction Cost Economics, the likelihood of focal buyers to exhibit opportunism was explored with partial least squares (PLS) structural equation modeling (SEM) and transaction costs were used to identify the factors that affect the farmers/contractors? choice of market channel (using market shares) through a two-limit Tobit model. Findings show that opportunism is not rampant among focal buyers of mango. In the PLS_SEM, it was found out that asset specific investments significantly increase supplier dependency and supplier dependency and supplier dependency and focal buyer dependency do not significantly affect focal buyer opportunism. On the other hand, buyers? uncertainty is almost significant in increasing the level of focal buyer opportunism. Furthermore, focal buyer opportunism was not seen as a significant factor for choosing a focal buyer for mango. However, males were found to sell to their focal buyers less than women do, farming experience decreases the marketing share of their respective focal buyer while farm services increases it, and lastly, transportation effort by the buyer increases his/her marketing share. These findings suggest practical insights in controlling focal buyer opportunism and increasing marketing shares of fresh mango buyers.